From maize flour to bread: assessing the impact of processing on phenolic and volatile composition - Silva, Andreia Leonor Vieira Bento da (2022)
Broa is a Portuguese ethnic bread traditionally prepared from maize open pollinated varieties (OPVs). These traditional varieties have been threatened by the progressive introduction of hybrid varieties, which do not possess the ability to produce high-quality broas and are less resilient to adverse environmental conditions. Scarce scientific studies have been reported regarding the nutritional and sensorial quality of broas and traditional Portuguese maize varieties. This work aimed to address this gap by providing information on the phenolic and volatile composition of broas and maize OPVs, important quality parameters in foods, related to health benefits and sensory attributes. Results showed that Portuguese maize OPVs and broas are a valuable source of phenolic compounds, in particular hydroxycinnamic acids and hydroxycinnamic acid amides (HCAAs). Several HCAAs were tentatively identified for the first time. Phenolic compounds not only resisted to the bread making process, but their free content also increased, suggesting that their bioaccessibility was improved. The traditional OPVs and corresponding broas showed higher phenolic contents when compared with a commercial maize flour and broa. The major volatiles detected in maize flours and broas were aldehydes derived from lipid oxidation reactions. Other compounds, derived from bread making, as pyranones, were also detected in broas. According to the results from a sensory panel evaluation, broas with higher contents in pyranones and lower in aldehydes were preferred by the consumers. Phenolic compounds appear to inhibit lipid oxidation reactions and increase browning reactions during bread making and, consequently, origin broas with better sensory characteristics. In addition, results suggested that a more advanced technique (comprehensive two-dimensional gas chromatography) is able to unveil relevant volatile compounds, since it allowed the detection of minor volatiles which may significantly influence broas overall aroma, as sulphur compounds. Overall, the results obtained in this work reinforce the importance of preserving these valuable genetic resources.